The Analysis of Pedagogic Competency Culinary Teacher of Implementation Curriculum 2013 - Suartana, I Ketut; Indah Kumari Dely, Ni Kadek (LPPM Undiksha, 2017)
The purpose of this study was (1) to describe the pedagogical competence of teachers in the majoring in culinary on the implementation of Curriculum 2013; (2) to describe the obstacles culinary experienced teachers in the implementation of Curriculum 2013. This study used a qualitative research with case studies (qualitative case study) to obtain in-depth information regarding the implementation of Curriculum 2013. The study was conducted in seven vocational schools in the Badung regency who implements 2013. The school curriculum is used in this research was determined by purposive sampling with the base CMS implements the curriculum of 2013. The subjects were all teachers Hospitality in vocational teaching in classes X, XI, and XII are used as a place of research. Meanwhile the object of this study is the pedagogical competence of teachers in curriculum implementation 2013. Data collection techniques used in this study includes observational techniques non participants, documentation, and semi-structured interview. Observation techniques are used to seeing the implementation of learning majoring in food service in class X, IX and XII to implement ccurriculum 2013 interview techniques used to obtain information readiness, obstacles to teachers in implementing appropriate learning in the majoring in culinary Curriculum 2013. The conclusions of this study were: 1) pedagogical competence of teachers catering services in Badung are in accordance with the demands of the curriculum, 2013. In connection with the activities Teacher Performance Assessment there are 7 (seven) aspects and 46 (forty six) indicators developed in respect of mastery pedagogical competence according to Regulation No. 74 of 2008. From the findings, it seemed that all the indicators have been achieved with the criteria very well. With excellent ability pedagogical competence will allow teachers to implement the curriculum in 2013, especially in the culinary learning.